2000
DOI: 10.1097/00007890-200007270-00016
|View full text |Cite
|
Sign up to set email alerts
|

Epitope Analysis of Hla Class I Donor Specific Antibodies in Sensitized Renal Transplant Recipients

Abstract: Our data show that a small number of private and public alloepitopes seem to be responsible for antibody production in patients sensitized from a previous graft. A detailed description of these HLA-epitopes, in the context of clinical graft complications, may lead to an improved organ allocation strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
10
1
Order By: Relevance
“…It is important to emphasize that the FlowPRA class I Single Antigen technique allowed us to identify most of the antibodies specific for antigens sharing the same immunizing epitopes in each serum sample. Contrary to a recent report (18), our study showed that only five of the 55 (9%) anti-HLA class I-positive patients developed alloantibodies with specificity restricted to the mismatched HLA-A or -B antigen/s of the graft, that is to say alloantibodies specific for the "private" epitopes of the mismatched donor HLA class I molecules. A broad HLA-A and/or -B sensitization was found in more than 90% of the study population.…”
Section: Discussioncontrasting
confidence: 99%
“…It is important to emphasize that the FlowPRA class I Single Antigen technique allowed us to identify most of the antibodies specific for antigens sharing the same immunizing epitopes in each serum sample. Contrary to a recent report (18), our study showed that only five of the 55 (9%) anti-HLA class I-positive patients developed alloantibodies with specificity restricted to the mismatched HLA-A or -B antigen/s of the graft, that is to say alloantibodies specific for the "private" epitopes of the mismatched donor HLA class I molecules. A broad HLA-A and/or -B sensitization was found in more than 90% of the study population.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, 3-83 B cells, alloantibodies, and immune complexes are more likely to enhance T cell activation through the indirect presentation pathway in vivo. We therefore theorize that the increased frequency of allospecific T cells observed in the ELISPOT assay reflects not only alloreactive T cells that were activated via the indirect pathway, but also alloreactive T cells that become activated by the direct pathway; these cells may have become activated by the process of epitope spreading (55) or by the semidirect pathway described by Lechler and colleagues (56).…”
Section: Discussionmentioning
confidence: 98%
“…A consensus is emerging that donor-specific Abs (DSAs) are predictive of poor graft outcome (30,31), and the activation of complement downstream of DSA binding to graft endothelium comprises the currently accepted paradigm for the mechanistic basis of how DSA effects graft loss (32). The observations in this study challenge the limited scope of this paradigm and demonstrate the ability of alloantibodies to function as opsonins to facilitate CD40-CD154-independent T cell activation and the rejection of allogeneic heart and skin grafts.…”
Section: Discussionmentioning
confidence: 99%